2019
DOI: 10.1155/2019/6527175
|View full text |Cite
|
Sign up to set email alerts
|

Influence Analysis of Underground Excavation on the Adjacent Buildings and Surrounding Soil Based on Scale Model Test

Abstract: In urban areas, it is common to construct underground structure nearby existing buildings. To investigate the impact of excavation construction on the adjacent existing buildings and surrounding soil, eight parallel scale model tests that considered the process of cut and cover construction are carried out with two kinds of the diameter of support piles, two kinds of the adjacent structure, and two kinds of the relative horizontal distance from the excavation in the laboratory. And, the variations of horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…There is an upward uplift state on the left side, which is affected by the boundary and can be ignored. There is a large amount of surface settlement in the area under the middle line of the cross-passage, and the settlement gradually decreases with the increase of the distance between the two sides of the middle line of the cross-passage (Guo et al, 2018;Jiang et al, 2018;Zhang et al, 2018a;Yu and Geng, 2019). When the second Frontiers in Earth Science frontiersin.org 10 layer guide tunnel is excavated through the existing line, it has little influence on the surface settlement and track settlement.…”
Section: Stratum Subsidencementioning
confidence: 99%
“…There is an upward uplift state on the left side, which is affected by the boundary and can be ignored. There is a large amount of surface settlement in the area under the middle line of the cross-passage, and the settlement gradually decreases with the increase of the distance between the two sides of the middle line of the cross-passage (Guo et al, 2018;Jiang et al, 2018;Zhang et al, 2018a;Yu and Geng, 2019). When the second Frontiers in Earth Science frontiersin.org 10 layer guide tunnel is excavated through the existing line, it has little influence on the surface settlement and track settlement.…”
Section: Stratum Subsidencementioning
confidence: 99%
“…is FE code has been applied successfully in solving many geotechnical problems such as slope stability [41], soil-structure interactions [42][43][44], excavations [45][46][47][48], tunnelling [49], and fluid-mechanical interactions [50].…”
Section: Finite Element Codementioning
confidence: 99%
“…e first level of props was installed at 2.0 m below the ground surface. e props are modeled as soft with axial rigidity of 81 × 10 3 kNm [21][22][23][24][25][26]. A 60 m high, 15 m wide 20storey, concrete building with three spans in each direction was selected in the study.…”
Section: Development Of Three-dimensional Finite Element Modelmentioning
confidence: 99%
“…Among those numerical studies, however, responses of the framed building to excavation were reported in a limited number of studies. Most of these aforementioned research studies only examined the tunnelling effects on buildings founded on shallow footings [21][22][23][24]. erefore, there is a gap of systematic research on the responses of a high-rise building subjected to live load and resting on the piled raft to advancement of adjacent excavation.…”
Section: Introductionmentioning
confidence: 99%